Bereavement, multimorbidity and mortality: a population-based study using bereavement as an indicator of mental stress. Issue 9 (30th August 2017) - Prior, A.; Fenger-Grøn, M.; Davydow, D. S.; Olsen, J.; Li, J.; Guldin, M.-B.; Vestergaard, M.
Abstract: Background: Mental stress is associated with higher mortality, but it remains controversial whether the association is causal or a consequence of a higher physical disease burden in those with a high mental stress load. Understanding causality is important when developing targeted interventions. We aimed to estimate the effect of mental stress on mortality by performing a 'natural' experiment using spousal bereavement as a disease-independent mental stressor. Methods: We followed a population-based matched cohort, including all individuals in Denmark bereaved in 1997–2014, for 17 years. Prospectively recorded register data were obtained for civil and vital status, 39 mental and physical diagnoses, and socioeconomic factors. Results: In total, 389 316 bereaved individuals were identified and 137 247 died during follow-up. Bereaved individuals had higher all-cause mortality than non-bereaved references in the entire study period. The relative mortality in the bereaved individuals was highest shortly after the loss (adjusted hazard ratio (aHR), first month: 2.50, 95% confidence interval (CI) 2.37–2.63; aHR, 6–12 months: 1.38, 95% CI 1.34–1.42). The excess mortality rate associated with bereavement rose with increasing number of physical diseases (1.33 v. 7.00 excess death per 1000 person-months for individuals with 0 v. ⩾3 physical conditions during the first month) and was exacerbated by the presence of mental illness. The excess mortality among bereaved individuals was primarily due to death from natural causes. Conclusions: Bereavement was associated with increased short-term and long-term mortality, even after adjustment for morbidities, which suggests that mental stress may play a causal role in excess mortality.